Satellite-Based Quantum Key Distribution for Remote Secure Communication - Martinez, Isabel; Cruz, Miguel de la; Gonzales, Samantha (Journal of Tecnologia Quantica, 2024)
The background of this research focuses on the challenges of remote communication security in the ever-evolving digital era. Satellite-based Quantum Key Distribution (QKD) was chosen as a solution to address security concerns by utilizing the principles of quantum mechanics. The purpose of this study is to evaluate the effectiveness of satellite-based QKD in dealing with atmospheric disturbances and to identify factors that affect the performance of the system under varying weather conditions. The method used is a field experiment by transmitting quantum photons through satellites under various weather conditions and measuring the success rate of signal transmission. The results show that the influence of weather, especially rain and thick clouds, can reduce the success of signal transmission by up to 50%. However, in sunny weather conditions, the success rate reaches 95%. The conclusion of this study is that although satellite-based QKD promises secure communication solutions, atmospheric challenges are still a major obstacle, requiring further development in protocols and technologies to overcome such interference. This research makes an important contribution to the development of satellite-based QKD for safer global communication.